IMPLEMENTATION OF THE THINK PAIR SHARE TYPE COOPERATIVE LEARNING MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES IN THE PKN SUBJECT IN GRADE V OF MI - Nurmanita, Mutiara; Arhanuddin, Arhanuddin; Nurhayati, Nurhayati; Nento, Shinta; Tinungki, Nurlaila (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
ABSTRACT This study aims to examine the effectiveness of implementing the cooperative learning model Think Pair Share in improving students' academic achievement in the subject of Civics Education (PKN) in Grade V at MI At-Taqwa Manado. The research problem addressed is how the application of the Think Pair Share cooperative learning model contributes to improving student learning outcomes in Civics Education for Grade V at MI At-Taqwa Manado. The research employed a classroom action research (CAR) approach based on the Kurt Lewin model, which consists of four main stages: planning, action implementation, observation, and reflection. Data collection was carried out using three methods: observation, testing, and documentation. The study was conducted in Grade V at MI At-Taqwa Manado, involving a total of 25 students. The findings indicate that the application of the Think Pair Share cooperative learning model has a positive impact on increasing student engagement in the learning process as well as their academic performance. In the first cycle, teacher activity improved from 50 to 95.83, student learning activity increased from 2.36 to 3.24, and the percentage of students achieving mastery learning rose from 60% to 92% in the second cycle. Therefore, the material delivered through the Think Pair Share cooperative learning model effectively enhances student learning outcomes in Civics Education at MI At-Taqwa Manado. ABSTRAK Penelitian ini bertujuan untuk mengkaji efektivitas penerapan model pembelajaran kooperatif jenis Think Pair Share dalam meningkatkan prestasi belajar siswa pada mata pelajaran Pendidikan Kewarganegaraan di kelas V MI At-Taqwa Manado. Permasalahan yang dikaji dalam penelitian ini yaitu bagaimana penerapan model pembelajaran kooperatif tipe Think Pair Share berkontribusi terhadap peningkatan hasil belajar peserta didik pada mata pelajaran PKN di kelas V MI At-Taqwa Manado. Penelitian ini menggunakan jenis penelitian tindakan kelas (PTK) dengan pendekatan model Kurt Lewin, yang mencakup empat tahapan utama: perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Pengumpulan data dalam penelitian ini dilakukan melalui tiga metode, yaitu observasi, tes, dan dokumentasi. Penelitian dilaksanakan di kelas V MI At-Taqwa Manado yang terdiri atas 25 siswa. Temuan penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif tipe Think Pair Share berdampak positif terhadap peningkatan keterlibatan siswa dalam proses pembelajaran serta hasil belajar mereka. Pada siklus I peningkatan aktivitas pendidik sebesar 50 meningkat menjadi 95,83, aktivitas peserta didik dalam pembelajaran sebesar 2,36 meningkat menjadi 3,24, dan peserta didik yang mendapatkan ketuntasan belajar sebesar 60% meningkat menjadi 92% pada siklus II. Jadi materi yang diberikan dalam model pembelajaran kooperatif tipe Think Pair Share dapat meningkatkan hasil belajar siswa pada mata pelajaran PKN di MI At-Taqwa Manado.